Lomba Game Based Learning Anti Korupsi (PAK) Sekolah-Sekolah di Salatiga - Christina Maya Indah Susilowati; Sri Harini Dwiyatmi; Rahmadini Eka C. Van Hanoch; Rasendria Bimo Permana (Jurnal Hukum Lex Generalis, 2025)
The purpose of the Community Service Program with the aforementioned title is to express appreciation for anti-corruption activists in Salatiga City, conducted by elementary and junior high school teachers in Salatiga City. They have previously participated in the anti-corruption game-based learning workshop held by the Salatiga City Regional Inspectorate. In addition to providing appreciation, this Game-Based Learning Competition also implements the knowledge gained in the aforementioned 9 core anti-corruption values ​​workshop. Through this workshop, participants are expected to create anti-corruption games based on the 9 core anti-corruption values ​​and implement them in their respective schools. This competition serves not only as an appreciation but also as a means of assessing the extent to which schools have created and implemented anti-corruption education based on the 9 core anti-corruption values. It turns out that some of the participants in this Game-Based Learning Competition have evaluated the game tools they created, even replicated the games, and some have even patented their game methods.